Effect of Attachment Training on Anxiety and Attachment Behaviors of first-time Mothers - Monireh Toosi; Marzieh Akbarzadeh; Najaf Zare; Farkhondeh Sharif (Tehran University of Medical Sciences, 2011)
Background & Aim: Pregnancy experience can be a kind of crisis in women&aposs lives. Different forms of anxiety can make problems in pregnant women. This study aimed to determine the effect of attachment education on anxiety and attachment behaviors of first-time mothers. Methods & Materials: In this clinical trial, 84 primigravida women were selected from two hospitals in Shirazi using convenience sampling. The participants were randomly allocated to the test and control groups. Data were collected using a personal data form, the Anxiety Inventory Spielberger, and the maternal infant attachment tab view. The intervention group received four two-hour sessions during one month training course on attachment behavior. Maternal attachment behaviors were shaped Weekly on the forms. The control group received usual care of pregnancy. At the first day after the delivery, the researchers observed mothers attachment behavior during breastfeeding in all groups using Avant sheet without informing the mothers. Data were analyzed using statistical tests such as Chi-square, T-test, and paired t-test. Results: The mean of the anxiety score was no significantly different before the intervention between the groups (P=0.59). The average anxiety scores was statistically significant after the intervention in the two groups (P=0.003). Also, average scores on the attachment of mothers with the breastfeeding infants was statistically different (P<0.001) in the intervention group. Conclusion: Attachment behavior training reduces anxiety and increases maternal attachment.